CHITINOLYTIC BACTERY ACTIVITY ISOLATED FROM THE MUD FIELDS - Nuniek Herdyastuti; Sari Edi Cahyaningrum; Tri Joko Raharjo; Mudasir; Sabirin Matsjeh (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2010)
A chitinolytic microorganism had been isolated from mud fields in Ketintang Surabaya area by using a minimal media containing 0.4% colloidal chitin. Activity assay is based on released N-acetyl-glucosamine which reacted with 3,5 dinitrosalicyclic acid. Mud fields produce 63 bacterial isolates with chitinase activity (TNH1 – TNH63 isolates). The highest activity was shown by TNH11 isolate with specific activity 1.27 U/mg. TNH11 isolates was Gram negative, rod-cocoid cell, has a colony of yellow, round shape, convex elevation, flat margin and the colony diameter 3–5 mm.